2019
DOI: 10.1177/2332858419868158
|View full text |Cite
|
Sign up to set email alerts
|

Smart but Evil? Student-Teachers’ Perception of Educational Researchers’ Epistemic Trustworthiness

Abstract: In-service and preservice teachers are increasingly required to integrate research results into their classroom practice. However, due to their limited methodological background knowledge, they often cannot evaluate scientific evidence firsthand and instead must trust the sources on which they rely. In two experimental studies, we investigated the amount of this so-called epistemic trustworthiness (dimensions expertise, integrity, and benevolence) that student-teachers ascribe to the authors of texts who prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 89 publications
2
29
2
Order By: Relevance
“…The first author once testified before a state senate education committee and was surprised to hear senators sarcastically noting that researchers can make their studies say whatever they want. From an empirical perspective, Merk and Rosman (2019) found evidence that student-teachers held a "smart but evil" stereotype about education researchers, "as the authors of scientific studies … are perceived not only as less benevolent, with less integrity, but also as having more expertise in contrast to practitioners. This is an intriguing finding, as it suggests that student-teachers hold a kind of distrust in scientists" (p. 6).…”
Section: Increased Use Of Replication Is Neededmentioning
confidence: 99%
“…The first author once testified before a state senate education committee and was surprised to hear senators sarcastically noting that researchers can make their studies say whatever they want. From an empirical perspective, Merk and Rosman (2019) found evidence that student-teachers held a "smart but evil" stereotype about education researchers, "as the authors of scientific studies … are perceived not only as less benevolent, with less integrity, but also as having more expertise in contrast to practitioners. This is an intriguing finding, as it suggests that student-teachers hold a kind of distrust in scientists" (p. 6).…”
Section: Increased Use Of Replication Is Neededmentioning
confidence: 99%
“…(2020) recently edited a Special Topic for AERA Open which published some of the first registered reports in educational psychology, including findings on student-teacher relationships (Robinson, Scott & Gotfried, 2019), pre-service teacher perceptions of researcher trustworthiness (Merk & Rosman, 2019), text framings for nudges to improve college matriculation (Kramer, 2020), and identification policies for gifted education assignment (Peters et al, 2019).…”
Section: Pre-registration and Registered Reportsmentioning
confidence: 99%
“…In line with such arguments, Merk and Rosman (2019) found what they subsequently called the "smart but evil" stereotype: In two experimental studies, they showed that preservice teachers view educational researchers' expertise as 2 significantly higher than their integrity and benevolence compared with their views on practitioners (i.e., in-service teachers). While it is still disputed whether comparably lower-but still high-integrity and benevolence ascriptions may indeed be labeled as "evil" (Hendriks et al, 2021), Hendriks et al (2021) found additional (partial) support for a smart but evil pattern in preservice teachers: When following the epistemic aim of acquiring theoretical explanations in a teaching context, they saw researchers as having more expertise and integrity but less benevolence compared with practitioners.…”
mentioning
confidence: 93%